GENERAL DIDACTIC PRINCIPLES OF TEACHING A FOREIGN LANGUAGE - avezova, nigora (Центр Научных Публикаций (buxdu.uz), 2021)
The learning process is very extensive and it is difficult to imagine that all the principles can be significant for the entire process. Under the principles of training, it is considered to be the main provisions that determine the nature of the learning process, which are formed on the basis of the chosen direction and the approaches corresponding to this direction. Clearly formulated training principles will help you decide how and what kind of training content to select, what materials and techniques to use